The study of peripherally inserted central catheterizations in Neonatal Intensive Care Unit, Maharaj Nakorn Chiang Mai Hospital - Thongsawang, Sariya; Inta, Nonglak; Kunapun, Sukonta (Biomedical Sciences and Clinical Medicine, 2016)
Objective To determine the clinical characteristics of newborns who had peripherally inserted central catheterizations (PICCs) and complication rates. Methods This was a retrospective descriptive study of newborns who underwent PICCs placement on the neonatal intensive care unit at Maharaj Nakorn Chiang Mai Hospital form January 1, 2011 to December 31, 2015. Data from electronic medical records were compiled, including the demographic data, the PICCs insertion records and complications. Data were analyzed using descriptive statistics, incidence rates and binary logistic regression. Results A total of 73 newborns with PICCs placements were analyzed. Sixty- nine (94.5%) newborns were less than 37 weeks gestational age; 46 (63.0%) were inserted PICCs at 1-10 days of age; 49 (67.1%) were very low birth weight infants (<1,500 grams), and 44 (60.3%) were inserted PICCs at body weight less than 1,500 grams. Forty-one newborns (56.2%) had duration of insertion for PICC less than 14 days, while 30 (41.1%) had administrated the total parenteral nutrition more than 30 days. Seventy-two (98.6%) used 1-French catheters. All the catheters were inserted into the antecubital vein. The most indications for PICCs placement were used for total parenteral nutrition (93.2%). The majority of PICCs were removed because no longer required (71.2%). PICCs complications occurred in 8 cases (10.9%). All of the complications were extravasations. The incidence rate of complications was found to be 7.1 per 1000 catheter days. The results revealed that body weight at PICCs insertion was a significant related to the PICCs complications. It indicatedthat body weight >1,500 gms is 11 times higher for PICCs complications than body weight < 1,500 gms (OR= 10.7, p=.01, 95% CI= 1.64-70.0). Conclusion The results of this study provide baseline information in consideration of the provision PICCs placement, used to develop guidelines and management of PICCs in neonatal intensive care unit, especially in newborns weighing >1,500 gms at risk of extravasation.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />